Installing e-commerce as a purchase function for an industrial sector company - Santos, Adriana de Paula Lacerda; Santos Filho, Mauro Lacerda (Revista Gestão da Produção Operações e Sistemas, 2008)
This paper is the product of a research project about the introduction of e-commerce in the purchasing processof the industrial companies. The report presents the main results about the application of the method during aneighteen months time period, related with the study of the functioning of the purchasing procedures of the companiesbefore and after the implementation of the e-commerce in the purchasing process for the office materialsby one large industry.Keywords: e-commerce, purchasing, office materials